Presentation: To Think the Fifth Centenary (I) - Glave, Luis Miguel (1990)
Madrid, 1565, Francisco de Morales had returned to his land after spending twenty years serving God and the Christian king in Peru. Before, just a decade after arriving in the Inca kingdom, the conquerors entered a tense process of colonial establishment. It was a time when nothing could be simple, fast, or definitive; internecine wars between them, violence at all levels and social classes, disagreements on the terms through which the conquest of the territory that was beginning to be called Peru was justified and regarding the type of society that was intended to be founded.